Gambaran Perbedaan Kadar Timah (Sn) pada Air Buah dan Buah Dalam Kemasan Kaleng - Rahmawati Rahmawati; Muh. Rifo Rianto; Effendy Rasiyanto; Hasrianti Hasrianti (Lontara Journal of Health Science and Technology, 2020)
Canned fruit is fruit that is packaged in packaging, using cans through many processes, aiming to maintain the durability of the packaged fruit. The packaging uses cans made of several heavy metals, one of which is tin (Sn). The process of preserving fruit, which goes through many stages, may allow the heavy metal to be hydrolyzed, causing the canned fruit to contain heavy metals which can be harmful to human health. This study aims to determine and determine the description of differences in tin (Sn) content in fruit water and canned fruit. The type of research used is laboratory observation with simple random sampling technique. Based on the results of research from 5 samples of canned fruit, the results obtained were the results of research on sample A (fruit) 3.19 mg / kg (water) 2.18 mg / L, B (fruit) 5.08 mg / kg (water) 0.49 mg / L, C (fruit) 1.08 mg / kg (water) 0.74 mg / L, D (fruit) 1.28 mg / kg (water) 1.56 mg / L, E (fruit) 2.92 mg / kg (water) 2.78 mg / L). This research can be concluded that of the 5 samples studied contained levels of lead (Sn) below the maximum threshold for food contamination set by BPOM in 2009, namely 250 mg / kg so it is still safe for consumption, and the levels of lead (Sn) obtained at fruit is higher than the tin content in fruit water in cans.